The Routes of Emergence of Life from LUCA during the RNA and Viral World: A Conspectus - Jheeta, Sohan (Life (Basel), 2015)
How did life emerge on Earth? The aim of the Network of Researchers on Horizontal Gene Transfer and the Last Universal Cellular Ancestor (NoR HGT & LUCA) is to understand how the genetics of LUCAs were reorganised prior to the advent of the three domains of life. This paper reports the research of eminent scientists who have come together within the network and are making significant contributions to the wider knowledge base surrounding this, one of science’s remaining mysteries. I also report on their relevance in relation to LUCAs and life’s origins, as well as ask a question: what next?